Uncommon cause of pain abdomen in an end-stage renal disease patient on hemodialysis - Ramanjit Singh Akal; Vijoy Kumar Jha; Deep Yadav; Ramendra Singh Sikarwar (Wolters Kluwer Medknow Publications, 2024)
Pain abdomen is an unusual symptom in an end-stage renal disease (ESRD) patient, and the causes of the same have not been clearly defined. The causes may be related to advanced azotemia causing esophagitis, gastritis, and peptic ulcer disease or pressure-related pain due to polycystic kidney disease. The causes may be totally unrelated to chronic kidney disease (CKD) and may present due to surgical causes such as cholelithiasis, appendicitis, diverticulitis, acute mesenteric ischemia, and others. We report an unusual case of pain abdomen in an 11-year-old child of CKD on maintenance hemodialysis (MHD) who presented with recent onset left-sided hypochondriac pain and swelling. His contrast-enhanced computed tomography abdomen showed a large hydatid cyst in the spleen, and the patient underwent partial cystectomy for the same. Histopathological examination confirmed the diagnosis of splenic hydatid cyst. The postoperative course was uneventful. There are only a few case reports of isolated splenic hydatid cyst reported from India, but to the best of our knowledge, the same has never been reported in a child with CKD on MHD making it an unusual cause of pain abdomen in ESRD patients.